Enhanced visible light photocatalytic reduction of cr (vi) by bi2wo6 nanosheet/cufe2o4 nanofiber heterojunctions - Musa, Makiyyu Abdullahi; Shao, Hong; Xu, Da; Sun, Feng; Dong, Xiangting; Azis, Raba'ah Syahidah; Ugya, Adamu Yunusa; Ari, Hadiza Abdullahi (Elsevier, 2023)
Heterojunction formation is among the important approaches to improve visible light activity of photocatalysts, to achieve cheaper and more sustainable pollutant removal, at larger scale. In this study, Bi2WO6 NS/x CuFe2O4 NF (x = 1, 2, 5 and 10) composites were prepared using electrospinning and hydrothermal synthesis, to achieve improved photocatalytic Cr (VI) removal under visible light. The effects of the composite formation on their structural, optical and photocatalytic properties were studied. Pure CuFe2O4 and Bi2WO6 phases were achieved, as reflected by X-ray diffraction (XRD) analysis, with some variations in peak parameters in the Bi2WO6 NS/CuFe2O4 NF composites, which confirmed the incorporation of the CuFe2O4 NFs into the Bi2WO4 NS. From photoluminescence studies, lower emission peaks were observed in the Bi2WO6 NS/CuFe2O4 NF composites than that in pure Bi2WO6 NS, indicating the achievement of suppressed recombination of charge carriers in the composites. Hence, Cr (VI) removal rate was significantly improved with the Bi2WO4 NS/ CuFe2O4 NF composite formation, where each of them shows higher activity than both Bi2WO6 NS and CuFe2O4 NF. The highest removal rates of 90.35 and 96.04 were achieved with the sample Bi2WO4 NS/2 CuFe2O4 NF, after 60 and 120 min of visible light irradiations respectively.